Samarium(III) Triflate as an Efficient and Reusable Catalyst for the Facile Synthesis of 1,2,4,5-Tetrasubstituted Imidazoles - Gorepatil, A.; Gorepatil, P.; Gaikwad, M.; Ghumare, A.; Mali, J.; Ingle, V. (Journal of Scientific Research, 2023)
An efficient, simple, and green four-component reaction for synthesizing 1,2,4,5-tetrasubstituted imidazoles is developed. In present work exploring the use of Samarium triflate as a heterogeneous catalyst for the four-component reaction of aldehydes, aromatic amines, benzil, and ammonium acetate. The current approach offers many advantages, such as excellent yields, shortening of reaction time, reusability of catalyst, and use of mild reaction conditions.